Biodegradable Polymers: Properties, Applications, and Environmental Impact - Dallaev, Rashid; Papež, Nikola; Allaham, Mohammad M; Holcman, Vladimír (Polymers, 2025)
The accelerating global demand for sustainable materials has brought biodegradable polymers to the forefront of scientific and industrial innovation. These polymers, capable of decomposing through biological processes into environmentally benign byproducts, are increasingly seen as viable alternatives to conventional plastics in sectors such as packaging, agriculture, and biomedicine. However, despite significant advancements, the field remains fragmented due to the diversity of raw materials, synthesis methods, degradation mechanisms, and application requirements. This review aims to provide a comprehensive synthesis of the current state of biodegradable polymer development, including their classifications, sources (natural, synthetic, and microbially derived), degradation pathways, material properties, and commercial applications. It highlights critical scientific and technological challenges-such as optimizing degradation rates, ensuring mechanical performance, and scaling up production from renewable feedstocks. By consolidating recent research findings and regulatory considerations, this review serves as a crucial reference point for researchers, material scientists, and policymakers. It strives to bridge knowledge gaps in order to accelerate the deployment of biodegradable polymers as integral components of a circular and low-impact material economy.
Keywords: environmental biodegradability; microbial fermentation; starch-based plastics; biodegradable polymers; renewable feedstocks; bioplastics; sustainable packaging; polylactic acid (PLA); polyhydroxyalkanoates (PHAs)